Education Revolution via Immersive Media: Leveraging Cultural AR Maps to Enhance Elementary Students’ Cultural Literacy - Neng Wulan; J. Julia; Kusman Rukmana (International Journal of Educational Qualitative Quantitative Research, 2026)
In the era of educational revolution, shifting from passive teaching to technology-driven interactive learning is crucial for cultivating cultural literacy in elementary education. This study evaluates the effectiveness of the Cultural AR Map, an innovative immersive media tool, in enhancing fourth-grade students' cultural literacy regarding socio-cultural diversity. Employing a quantitative quasi-experimental design with a nonequivalent control group, the investigation involved 60 students divided equally into experimental and control classes (n=30 each). Data gathered via standardized pretests and posttests were rigorously analyzed using Wilcoxon Signed-Rank and Mann-Whitney U tests alongside Normalized Gain (N-Gain) analysis. The results demonstrated a profound learning transformation in the experimental group, with mean literacy scores surging from 53.87 to 92.67, yielding a high N-Gain of 0.84 with an 83.62% effectiveness rating. Nonparametric analysis confirmed highly significant within-group improvements (Wilcoxon, p=0.000) and a statistically superior post-intervention performance in the AR-assisted class compared to the conventional PowerPoint-based class (Mann-Whitney, p=0.020). This study concludes that integrating immersive AR media revolutionizes cultural education by successfully translating abstract regional heritage into concrete, interactive, and explorable digital learning experiences. Practically, this research contributes a scalable technological framework for cross-disciplinary pedagogy, offering a robust model for interactive, culture-based digital curricula globally.